Treatise on sustainability science and engineering - Sikdar, S.K; Huang, Y.; Jawahir, I.S (Springer Netherlands, 2013)
This book is aimed at providing a comprehensive overview of recent developments in sustainability science and engineering. The book focuses on principles and practices and presents 18 interwoven chapters on four major themes:   Design for sustainability Sustainability metrics and analysis Sustainable energy Sustainable supply/value   Significant, state-of-the-art work, methodologies, practices and plans are presented by researchers, technology developers and industry leaders. Topics discussed include:   Life cycle assessment Product end-of-life options Practical approaches to sustainability Environmental footprint assessment Biofuels Sustainable supply chain management   The uniqueness of this book lies in the range of topics covered with in-depth analysis and case studies.   This book will be of interest to academic and industrial researchers, professionals in corporate and governmental organizations, and others interested in advancing the current state-of-the-art to the next level for the benefit of our global society.